Design and quality control of a pharmaceutical formulation containing natural products with antibacterial, antifungal and antioxidant properties - Ordóñez, Adriana (2009)
The aims of the present study were to determine the antibacterial and antifungal activity as well as mutagenicity of Sechium edule fluid extract and to obtain a pharmaceutical formulation with them. The extract exhibited antimicrobial activity against Escherichia coli, Klebsiella pneumoniae, Proteus mirabilis, Enterobacter cloacae, Serratia marcescens, Morganella morganii, Acinetobacter baumannii, Pseudomonas aeruginosa, Stenotrophomonas maltophilia, Candida spp. and Aspergillus spp. isolated from clinical samples from two hospitals of Tucuman, Argentina. Non-toxicity and mutagenicity on both Salmonella typhimurium TA98 and TA 100 strains until 100 μg/plate were observed. A hydrogel with carbopol acrylic acid polymer containing S. edule fluid extract as antibacterial, antimycotic and antioxidant agent was obtained. Microbiological, physical and functional stability of pharmaceutical formulation conserved at room temperature for 1 year were determined. Addition of antioxidant preservatives to store the pharmaceutical formulation was not necessary. The semisolid system showed antimicrobial activity against all Gram positive and Gram negative bacteria and fungi assayed. The minimal inhibitory concentration (MIC) values ranged from 20 to 800 μg/mL. Its activity was compared with a pharmaceutical formulation containing commercial antibiotic and antifungal. A pseudoplastic behavior and positive thixotropy were observed. Our current finding shows an antimicrobial activity of hydrogel containing S. edule extract on a large range of Gram negative and Gram positive multi-resistant bacteria and fungi. This topical formulation may be used as antimycotic and as antibacterial in cutaneous infections.